(untitled) (Perner’s Contacts, 2008)
Acid rain, disturbed ozone layer, danger of global warning and also risk of respiratory and cardiovascular diseases and other aspects of air pollution are results of emissions from power engineering, industry and transport. The article is focused on air pollution by air pollutants from transport and influence of these emissions on environment and also possibilities of reduction of their production. Possible solution of increasing concentration of polluting matters in the air is to substitute the fossil engine fuels for bio-fuels.